PERAN ORANG TUA DALAM MENGATASI KENAKALAN REMAJA DI DESA SEPPANG KECAMATAN UJUNG LOE KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
The main problem in this study is "How is the Role of Parents in Overcoming Juvenile Delinquency in Seppang Village, Ujung Loe District, Bulukumba Regency" with the formulation of the problem: 1. What are the impacts experienced by teenagers who fall into juvenile delinquency of alcoholic beverages in Seppang Village, Ujung Loe District, Bulukumba Regency? 2. What are the efforts of parents in overcoming juvenile delinquency of alcoholic beverages in Seppang Village, Ujung Loe District, Bulukumba Regency? This type of research is included in qualitative research using the approach method, namely: guidance approach and psychology approach. Furthermore, the data sources are primary data and secondary data. Then the data collection methods used are observation, interviews, and documentation. Then the data processing and analysis techniques are carried out through four stages, namely: Data reduction, data presentation, comparative analysis, and drawing conclusions. The results of this study indicate that the impacts experienced by adolescents who fall into juvenile delinquency of alcoholic beverages are two impacts, namely: 1. The impact of psychological and physical mental health of adolescents which causes adolescents to experience behavioral disorders, headaches and dependency, and 2. The impact on academic achievement of adolescents which causes adolescents to often sleep in class and decreased attendance. Efforts made by parents in overcoming juvenile delinquency of alcoholic beverages are two, namely: 1. Individual guidance by providing good examples/role models, and giving reprimands and punishments, 2. Group guidance by motivating adolescents to fill their free time with positive things, and village government programs in helping parents overcome adolescent promiscuity. The implications of this study are: 1. For adolescents to learn more and understand the impacts of juvenile delinquency due to alcohol, 2. For parents in Seppang Village as the people closest to their children, they should realize that their role is very large and can determine the direction of their children's future. Juvenile delinquency is a very serious problem, so parents must be able to overcome this problem by carrying out their roles well, 3. For the government to improve the facilities and infrastructure needed by adolescents to channel their talents and interests so that adolescents do not fall into juvenile delinquency due to alcohol, 4. The Seppang Village government and community leaders are expected to cooperate with parents of children in overcoming the problem of juvenile delinquency. Juvenile delinquency can be overcome if all parties are involved in this effort. Keywords: Role, Parent, Juvenile Delinquency, Liquor